La differenciation – « solution miracle » pour l’avenir de l’Union Europeenne? - Bogdana Petrică (Romanian Journal of European Affairs, 2009)
The differentiation has always accompanied the process of integration and it became more evident with the succession of enlargements. This concept originated in the practice of a tighter co-operation between some Member States in certain areas, or in the exceptional derogations given to other Member States which refused participation. Not only these exceptions may become the rule in an enlarged Union, but they appear as being the only solution, sometimes sensitive, and thus spring the need to be well organized. Beginning with the Treaties of Amsterdam and Nice the differentiation is legally enshrined, but it is the works of the Convention for the Drafting of the Constitutional Treaty that advanced the debate on this subject. Finally, the Lisbon Treaty kept most of the provisions of the Constitutional Treaty regarding this subject and for its ratification; it is precisely the concept of differentiation that we shall employ. The Irish “No” demonstrated once more the inevitable obstructions of the unanimity rule, and differentiation might be a solution, while still respecting the diversity of Member States.